Integrated Arrangement in Mass and Self-help Housing’s Infrastructure Based on Land Consolidation Approach - Wunas, Shirly; Veronica Natalia, Venny; Arifin, Mimi (International Journal of Engineering and Technology, 2019)
Horizontal housing development creates conflict between local communities and developers. The conflict leads to ineffective in land-uses and separated infrastructure networks. This paper focus on 1) analysing the arrangement of land parcels pattern among the local community, real-estate developers and their housings infrastructure network; 2) Composing the integrated infrastructure arrangement criteria for self-help and mass housing neighbourhood development based on land consolidations. The study location is Makassar suburban Area (South Sulawesi-Indonesia). Data was obtained from direct observation of each housing site arrangement. Method of analysis uses a qualitative method and spatial analysis. The results show: arrangements of housing parcel between the local communities and the real-estate developers show a different pattern. The land parcels belong to the community show irregular plots in a small range of land while the housings parcels belong to the real-estate developers are built in a wide-range area and regular parcels pattern. The infrastructure network for both types of housing is not integrated into the neighbourhood scale and further influences the urban infrastructure system. The integrated infrastructure arrangement for self-help and mass housing neighbourhood development based on land consolidations can be achieved by considering these criteria: a)Identify the land ownership; b) Measure the plots dimension as a start to land-banking process; 3) Expose the benefit of land consolidation; 4) Plan the blocks/plots and infrastructure network in participative ways with win-win solutionsÂ Â